Technical determinants of biathlon standing shooting performance before and after race simulation - Ihalainen, S.; Laaksonen, M. S.; Kuitunen, S.; Leppävuori, A.; Mikkola, J.; Lindinger, S. J.; Linnamo, V. (Scandinavian Journal of Medicine & Science in Sports, 2018)
The aim of this study was to identify performance-determining factors in biathlon standing shooting in rest and after intense exercise. Eight Finnish national- and nine junior-team biathletes participated in the study. Participants fired 40 resting shots (REST) and 2 × 5 competition simulation shots (LOAD) after 5 minutes of roller skiing at 95% of peak heart rate. Hit percentage, aiming point trajectory and postural balance were measured from each shot. Cleanness of triggering (ATV, movement of the aiming point 0-0.2 second before the shot) and vertical stability of hold (DevY) were the most important components affecting shooting performance both in REST (DevY, R = -0.61, P < .01; ATV, R = -0.65, P < .01) and in LOAD (DevY, R = -0.50, P < .05; ATV, R = -0.77, P < .001). Postural balance, especially in shooting direction, was related to DevY and ATV. Stability of hold in horizontal (F(1,15) = 7.025, P < .05) and vertical (F(1,15) = 21.285, P < .001) directions, aiming accuracy (F(1,15) = 9.060, P < .01), and cleanness of triggering (F(1,15) = 59.584, P < .001) decreased from REST to LOAD, accompanied by a decrease in postural balance. National- and junior-team biathletes differed only in hit percentage in REST (92 ± 8% vs 81 ± 8%, P < .05) and left leg postural balance in shooting direction in LOAD (0.31 ± 0.18 mm vs 0.52 ± 0.20 mm, P < .05), and the intense exercise affected the shooting technical components similarly in both national and junior groups. Biathletes should focus on cleanness of triggering and vertical stability of hold